Expectations and satisfaction of pregnant women: revealing prenatal care in primary care - Maciel Cardelli, Alexandrina Aparecida; Li Marrero, Tai; Pimenta Ferrari, Rosângela Aparecida; Trevisan Martins, Júlia; Serafim, Deise (Investigación y Educación en Enfermería, 2016)
Objective. To analyze the perception of primiparous women about prenatal care in Basic Health Units in a municipality in southern Brazil. Methods. This is a qualitative research from the perspective of Social Representation Theory, from the following question: How has been the pre-natal care for you? Eighteen pregnant women were interviewed. Results. The analysis resulted in three categories: Expectation representation about prenatal care; Rescuing the care offered in prenatal consultation; Unveiling the (dis) satisfaction with prenatal consultation. The prenatal care was apprehended as an essential moment for safe pregnancy, although centered on the doctor’s figure and guarantee access to early laboratory and imaging tests. On the other hand, dissatisfaction was revealed from the reception at the entrance to the health unit to the consultations access, although some statements suggest timely satisfaction. Conclusion. Prenatal care did not meet the specific expectations of the study group and unveiled that the nurse did not supply it, as a member of the multidisciplinary team. The organization of the nursing work process in primary care, related to prenatal care, needs to be revisited to promote the effectiveness of its actions. How to cite this article: Cardelli AAM, Marrero TL, Ferrari RAP, Martins JT, Serafim D. Expectations and satisfaction of pregnant women: revealing prenatal care in primary care. Invest. Educ. Enferm. 2016; 34(2):